la producción bananera y su impacto socioambiental en el sitio el sauce, cantón el guabo, año 2023 - Elizalde Armijos, Jenny Selena (Machala: Universidad Tecnica de Machala, 2024)
The present degree work “Banana production and its socio-environmental impact in the El Sauce site, El Guabo canton, year 2023-2024” has the purpose of detecting the socio-environmental problems in banana production in; soils, rivers, application of fertilizers and chemicals among others, in which it was thoroughly analyzed and related through scientific articles, bibliographic review and through the survey that was carried out on-site (place of the events) through the technique of the survey and interviews to understand first-hand the most essential problems on the site. In its context, it was discovered that there is a lack of knowledge on the subject of; application of agrochemicals, leadership and a pejorative labor and social relationship in the community. Thus, the general objective of the research is centered on “Establishing the socio-environmental impact generated by banana production at the El Sauce site in the El Guabo canton.” On the other hand, the research work is based on the Sociological Theory of Ecological Marxism founded by Karl Marx as well as Functionalism and Structuralism, both with a theoretical and methodological approach that seeks to understand the social, cultural or linguistic reality through the study of the underlying structures that organize and determine it. Consequently, the methodological approach applied in the research is quantitative, which allowed for a statistical analysis and modeling of relationships between the variables, which provided a more precise and objective understanding of the studied phenomena, which facilitated a more truthful and forceful interpretation. Based on the results obtained, it can be seen that they exist; internal social problems on the site, labor differences in agricultural activity which causes discomfort in the work environment, there is chemical contamination in the soil and rivers in banana plantations, likewise there is lack of knowledge when applying fertilizers and herbicides, such as also inexperience in how to use biosafety tools, according to the data that reflects the quality of life is medium-low, in addition there is lack of knowledge on the part of the board of directors on issues of leadership and management in public works among other problems that exist, all These difficulties are influencing and drastically affecting health, banana productivity, quality of life in people, based on what has been mentioned, the problem must be addressed promptly, from socio-environmental care as well as strengthening the community in leadership and good social relations, training and engaging both the site management and authorities and people related to the current problem in order to achieve collective well-being. Finally, based on the results collected, the intervention proposal called: “Design of a strategic plan to optimize the socio-environmental conditions and labor, social and personal relationships at the El Sauce site” is designed and implemented. It will help reduce environmental pollution through training, the people involved will be aware of how to correctly apply agrochemicals, and labor, social and personal relationships in the community will also be strengthened. Therefore, there will be operational planning and management according to the intervention of the problem that will be executed by the technical team responsible for the project, establishing time periods to evaluate and measure the results obtained and favorably meet the proposed intervention objectives. In that sense, there is an assigned budget that characterizes the viability of the project, from an effective technical, economic, social and environmental dimension.
El presente trabajo de titulación “La producción bananera y su impacto socioambiental en el sitio el Sauce, cantón El Guabo, año 2023-2024” tiene la finalidad de detectar los problemas socioambientales en la producción de banano en; suelos, ríos, aplicación de fertilizantes y químicos entre otros, en la cual se analizó y relacionó minuciosamente por medio de artículos científicos, revisión bibliográfica y a través de la encuesta que se realizó in-situ (lugar de los hechos) por medio de la técnica de la encuesta y entrevistas para entender de primera mano los problemas mas esenciales en el sitio. En su contexto, se pudo descubrir que existe un desconocimiento en tema de; aplicación de agroquímicos, liderazgo y una peyorativa relación laboral y social en la comunidad. De tal modo, el objetivo general de la investigación se centraliza en “Establecer el impacto socioambiental generado por la producción bananera en el sitio El Sauce del cantón El Guabo”. Por otra parte, el trabajo de investigación de se fundamenta en la Teoría Sociológica El Marxismo Ecológico fundamentado por Karl Marx como también el Funcionalismo y el Estructuralismo ambos con un enfoque teórico y metodológico que busca entender la realidad social, cultural o lingüística a través del estudio de las estructuras subyacentes que la organizan y determinan. Por consiguiente, el enfoque metodológico aplicado en la investigación es el cuantitativo la cual permitió realizar un análisis estadístico y modelar relaciones entre las variables, lo que proporcionó una comprensión más precisa como objetiva de los fenómenos estudiados, mismo que facilito una interpretación más verídica y contundente. En base a los resultados obtenidos se puede exteriorizar que existen; problemas sociales internos en el sitio, diferencias laborales en la actividad agraria lo que provoca malestar en el ambiente de trabajo, existe contaminación química en el suelo y ríos en las plantaciones de banano, así mismo existe desconocimiento al momento de aplicar fertilizantes y herbicidas, como también inexperiencia en cómo utilizar las herramientas de bioseguridad, de acuerdo a los datos que reflejan la calidad de vida es medio-bajo, además existe desconocimiento por parte de la directiva en temas de liderazgo y gestión en obras públicas entres otros problemas que existen, todas estas dificultades están incidiendo y afectando drásticamente en la salud, productividad de banano, calidad de vida en las personas , en función a lo mencionado la problemática debe ser atendida prontamente, desde el cuidado socioambiental como también fortaleciendo a la comunidad en liderazgo y buenas relaciones sociales, capacitándola y comprometiéndola tanto a la directiva del sitio como autoridades y personas relacionada al problema actual con el fin de lograr el bienestar colectivo. Por último, en base a los resultados recopilados se procede a diseñar e implementarse la propuesta de intervención que se denomina: “Diseño de un plan estratégico para optimizar las condiciones socioambientales y las relaciones laborales y personales en el sitio El Sauce” la cual ayudará a reducir la contaminación ambiental por medio de capacitaciones, las personas involucradas estarán al tanto como aplicar correctamente los agroquímicos, así mismo se fortalecerá las relaciones laborales, sociales y personales en la comunidad. Por ende, existirá una planificación y gestión operativa de acuerdo a la intervención del problema que serán ejecutadas por el equipo técnico responsable del proyecto, estableciendo periodos de tiempo para así, evaluar y medir los resultados obtenidos y cumplir favorablemente con los objetivos de intervención planteados. En ese sentido, se cuenta con el presupuesto asignado que caracterizan la viabilidad del proyecto, desde una dimensión técnica, económica, social y ambiental efectiva.
Keywords: SOCIAL; AMBIENTAL; AGROQUIMICOS; CONTAMINACION; LIDERAZGO